Properties of the delayed weighted gradient method - Andreani, Roberto (2022)
Funding Information: Roberto Andreani was financially supported by FAPESP (Projects 2013/05475-7 and 2017/18308-2) and CNPq (Project 301888/2017-5). Marcos Raydan was financially supported by the Fundação para a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) through the Project UIDB/MAT/00297/2020 (Centro de Matemática e Aplicações). Roberto Andreani would like to thank the Operations Research Group at CMA (Centro de Matemática e Aplicações), FCT, NOVA University of Lisbon, Portugal, for the hospitality during a two-week visit in December 2019. Funding Information: We would like to thank two anonymous referees for their comments and suggestions that helped us to improve the final version of this paper. Roberto Andreani was financially supported by FAPESP (Projects 2013/05475-7 and 2017/18308-2) and CNPq (Project 301888/2017-5). Marcos Raydan was financially supported by the Fundação para a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) through the Project UIDB/MAT/00297/2020 (Centro de Matemática e Aplicações). Roberto Andreani would like to thank the Operations Research Group at CMA (Centro de Matemática e Aplicações), FCT, NOVA University of Lisbon, Portugal, for the hospitality during a two-week visit in December 2019. Publisher Copyright: © 2020, Springer Science+Business Media, LLC, part of Springer Nature.